Prevention of Suicidality of Prisoners - Bogetić, Dragica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
Recognition, prevention and intervention are part of a multifactorial approach to reducing the suicide of convicts. Accordingly, the first goal of the paper is to point out the importance of a multifactorial and multidimensional model of responding to the suicide of convicts in prison, taking into account the following segments: suicide risk assessment; post-admission supervision and ensuring the safety of the suicidal convict; training of prison staff; key skills of intervention in case of suicide attempt; preventive activities by other convicts; multisectoral communications, in order to prevent the suicide of convicts. The second goal of the paper refers to the presentation of the CAPRA model as a proposal of tools in the training of prison staff and in solving the problem of suicide of convicts. The paper uses analysis and synthesis of theoretical and empirical findings through the study of relevant literature in various scientific data sources. Of importance for the prevention of suicide of convicts is the awareness of the prison administration and staff about the scientific knowledge in the field of prevention and treatment of suicide of convicts, and in order to decide on the most effective intervention, comprehensive and systematic knowledge of all factors of a multidimensional approach to preventive response is needed.